OPTIMALISASI FUNGSI HUMAS PEMERINTAH THE OPTIMIZATION OF GOVERNMENT PUBLIC RELATIONS FUNCTION - Sani, Anwar (Prodi Teknologi Pendidikan, 2014)
Abstract, world democratization forces many organizations including the government in this case, of all types in many regions of the world, to consider giving more attention to the government public relations activities. The role will include contributing to good governance and respect for human rights. That would mean public relations in Indonesia, as elsewhere in Asia, will be involved in the development of public diplomacy. Aware of the problems as well as the demands of optimization and revitalization of the role of public relations in the era of reform, democratization and transparency of public information, Indonesian Ministry of Home Affairs issued the Regulation of the Minister of the Home Affairs (Permendagri ) No. 13 of 2011, in which it sets the Implementation Guidelines for PR Tasks in the milieu of Ministry of Home Affairs and Local Government. The regulation represents the desire of the Ministry of Home Affairs to fix the government's role and functions of public relations in its internal milieu. The research question of this study concerns how the understanding of the public relations officer in the Ministry of Home Affairs of the Permendagri 13/2011 and how the implementation of Permendagri 13/2011 by public relations officials of Ministry of Home Affairs. The method used was qualitative method using the theory of social constructs of reality and symbolic interaction. The results showed that public relations officials in the Ministry of Home Affairs understood that the regulation was to improve the professionalism of Public Relations of the Ministry of Internal Affairs and as an effort to encourage the active participation of the public. While the background history of the regulation discovered in the implementation, there were efforts to socialize the regulation; its impacts, constraints and solutions related to its implementation and other four main public relations activities of the Ministry of Home Affairs which include public information services, public affairs, content analysis of media and crisis management.Key words : government public relations, Regulation of the Minister of the Home Affairs 13/2011Abstrak, demokratisasi dunia memaksa organisasi, termasuk juga pemerintah dalam hal ini, dari semua jenis di banyak wilayah di dunia untuk mempertimbangkan memberikan perhatian lebih pada aktivitas kehumasan pemerintah. Peran yang akan mencakup kontribusi bagi pemerintahan yang baik dan menghormati hak asasi manusia. Itu akan berarti hubungan masyarakat di Indonesia, seperti di tempat lain di Asia, akan terlibat dalam upaya pengembangan diplomasi publik.Sadar akan persoalan sekaligus tuntutan optimalisasi serta revitalisasi peran humas pemerintah di era reformasi, demokratisasi dan transparansi informasi publik, Kementerian Dalam Negeri Indonesia (Kemendagri) mengeluarkan Peraturan Menteri Dalam Negeri (Permendagri) Nomor 13 tahun 2011, yang di dalamnya mengatur Pedoman Pelaksanaan Tugas Kehumasan di Lingkungan Kementerian Dalam Negeri dan Pemerintah Daerah. Permendagri 13/2011 merepresentasikan keinginan Kementerian Dalam NegePertanyaan penelitian ini adalah bagaimana pemahaman para pejabat kehumasan di lingkungan Kemendagri terhadap Permendagri No.13 Tahun 2011 dan bagaimana implementasi Permendagri No.13 Tahun 2011 oleh pejabat kehumasan Kemendagri.Metode penelitian yang digunakan adalah metode kualitatif dengan menggunakan teori kostruksi sosial atas realitas dan interaksi simbolik.Hasil penelitian menunjukkan bahwa pejabat humas Kemendagri memahami Permendagri 13/2011 sebagai regulasi yang mendorong Humas Kemendagri untuk meningkatkan profesionalismenya dan merupakan upaya untuk mendorong partisipasi aktif publik. Sementara dalam implementasi Permendagri 13/2011 ditemukan beberapa latar belakang lahirnya Permendagri 13/2011, terdapat upaya sosialisasi Permendagri 13/2011, dampak, kendala serta solusi terkait implementasi Permendagri 13/2011 dan 4 aktivitas kehumasan utama Kemendagri yaitu layanan public information, public affairs, analisis isi media dan manajemen krisis.Kata Kunci : government public relations, humas pemerintahan, indonesia, permendagri 13/2011